Barista's Competency In Delivering Experiential Marketing In Coffee Shop In Bandung City - Alvarizy, Ahmad; Deliana, Yosini (Universitas Galuh Ciamis, 2021)
People have now made drinking coffee in coffee shops a new culture. Many people who are interested in getting into the coffee business because of the market potential are eager to explore the brewing process and want to share with those around them. One of the determinants of a coffee shop business success is the presence of a barista. Barista is the name for someone whose job is to make and serve coffee to customers. Therefore, baristas must have competence in delivering Experiential marketing such as treating customers as friends, remembering customers' names, and always smiling and baristas must have competence in accordance with the regulations of the Ministry of Manpower and Transmigration. The purpose of this research is none other than knowing the level of competence of baristas in conveying the values of experimental marketing and knowing the level of competence of baristas according to SKKNI No. 370 of 2013. This research was conducted using a questionnaire to baristas with quantitative techniques and conducting interviews with informants. The results of this study indicate that the majority of baristas are competent in applying this aspect of Experiential marketing. Based on the measurement of barista competence according to SKKNI Barista, it can be concluded that the majority of baristas are very capable of meeting the standards even though the majority of baristas do not know these standards and also only a small proportion of baristas who are respondents have attended Barista Schools.